Falconry Threatens Barbary Falcons in the Canary Islands Through Genetic Admixture and Illegal Harvest of Nestlings - Rodríguez, Beneharo; Siverio, Felipe; Siverio, Manuel; Rodríguez, Airam (Journal of Raptor Research, 2019)
Peregrine Falcons (Falco peregrinus) on the Canary Islands are considered to be of the Barbary Falcon subspecies (F. p. pelegrinoides). Here we report on lost falconry birds present among the wild population of resident falcons, and provide rough approximations of their abundance for Tenerife, the largest island of the Canaries. We observed lost falconry birds breeding with natural wild falcons, with at least one mixed pair producing fledglings. Only 54.1% of the breeding adults that we studied on the island showed typical Barbary Falcon plumage. Some nest sites were systematically poached, affecting the overall productivity of the population. Our findings suggest that the original Canarian Barbary Falcon population could be suffering from genetic mixing due to the presence of individuals originating from outside the population and from illegal harvest of nestlings. We recommend that local authorities continue to assess the degree of genetic admixture that occurs in this population, modify the current falconry regulations, implement management actions to prevent new escapes, eradicate exotic raptors, and put a stop to illegal nestling harvests. Peer Reviewed